Quantitative Study: Mathematics Learning Outcomes In Different Schools - Al Ayyubi, Ibnu Imam; Anggraeni, Ai Risma Sifa; Prayetno, Eko; Nurhikmah; Musaldin, La Ode (STIT Fatahillah, 2025)
This study aims to analyze the differences in students' mathematics learning outcomes across three schools: SD Yayasan Beribu, SDN 074 Ayudia in Bandung City, and SD Santa Maria Dolok Sanggul. The study involved the entire student population from these three schools, with samples of 20 students from SD Yayasan Beribu, 27 students from SDN 074 Ayudia, and 37 students from SD Santa Maria, totaling 84 students. The research focused on sixth-grade students at each of the schools. The study used a quantitative approach with a comparative method. The sampling technique employed stratified random sampling, and the data collection instrument was a test. The results show that the highest average learning outcome was obtained by SDN 074 Ayudia at 89.81, followed by SD Yayasan Beribu at 83.50, and SD Santa Maria at 82.43. The normality test indicated that the data were normally distributed, but the homogeneity test showed that the variance was not homogeneous (Sig. = 0.008). The ANOVA test revealed significant differences in mathematics learning outcomes between the three schools (Sig. = 0.000). Post Hoc analysis revealed significant differences between SD Yayasan Beribu and SDN 074 Ayudia, as well as between SDN 074 Ayudia and SD Santa Maria, but no significant difference between SD Yayasan Beribu and SD Santa Maria. This study emphasizes the importance of evaluating teaching practices to create more equitable learning outcomes across schools.